Modulation of the unfolded protein response by the human hepatitis B virus - Lazar, Catalin; Uta, Mihaela; Branza-Nichita, Norica (Frontiers in Microbiology, 2014)
During productive viral infection the host cell is confronted with synthesis of a vast amount of viral proteins which must be folded, quality controlled, assembled and secreted, perturbing the normal function of the endoplasmic reticulum (ER). To counteract the ER stress, cells activate specific signalling pathways, designated as the unfolded proteins response (UPR), which essentially increase their folding capacity, arrest protein translation and degrade the excess of misfolded proteins. This cellular defence mechanism may, in turn, affect significantly the virus life-cycle. This review highlights the current understanding of the mechanisms of the ER stress activation by Human Hepatitis B virus (HBV), a deadly pathogen affecting more than 350 million people worldwide. Further discussion addresses the latest discoveries regarding the adaptive strategies developed by HBV to manipulate the UPR for its own benefits, the controversies in the field and future perspectives.